(untitled) (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
Job satisfaction of employees is considered as important factor for the growth and success of any organization. However, many organizations have made minimal effort to assess the job satisfaction of employees including banks. This study aims to measure the job satisfaction of female employees and the major factors affecting it in commercial banks of Pokhara valley, Nepal. The study follows descriptive and explanatory designs. Purposive sampling technique was used in this research. The survey was conducted using a questionnaire administered to 150 female professionals working in different commercial banks of Pokhara valley. Descriptive statistics such as frequency analysis and mean score analysis, and inferential statistics such as correlation analysis and regression analysis were employed in this study. This study found that all the independent variables including promotion, supervisor behaviour, remuneration, working conditions and co-worker behaviour positively correlated with job satisfaction. Likewise, the study found that promotion, remuneration, and working condition have a significant impact on job satisfaction.